2009
DOI: 10.1007/s10152-009-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle and gonad development of the Northern Argentinean Mesodesma mactroides (Bivalvia: Mesodesmatidae)

Abstract: The reproductive cycle and gonad development of the yellow clam Mesodesma mactroides was studied over a period of 24 months (January 2005-December 2006 at the Argentinean sandy beach Santa Teresita. Histological examination of gonadal tissue revealed that sex ratios did not significantly deviate from the proportion of 1:1 and no case of hermaphroditism was found. The reproductive cycle of M. mactroides followed an annual cyclicality, which was significantly correlated to monthly mean sea surface temperatures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…In contrast, strong effects of temperature on the intraannual variation of reproduction of several shallow-water bivalves, including the surf clam M. mactroides, have been reported for the mid-temperate Atlantic beaches of South America, where the temperature seasonality is high (e.g. Defeo et al 1992, Morsan & Kroeck 2005, Fiori & Defeo 2006, Hermann et al 2009). In fact, between-ocean differences in thermal patterns have been suggested to explain differences in the biogeographic patterns of populations of the PanAmerican species Excirolana brasiliensis (Cardoso & Defeo 2004).…”
Section: Reproductive Cyclementioning
confidence: 96%
“…In contrast, strong effects of temperature on the intraannual variation of reproduction of several shallow-water bivalves, including the surf clam M. mactroides, have been reported for the mid-temperate Atlantic beaches of South America, where the temperature seasonality is high (e.g. Defeo et al 1992, Morsan & Kroeck 2005, Fiori & Defeo 2006, Hermann et al 2009). In fact, between-ocean differences in thermal patterns have been suggested to explain differences in the biogeographic patterns of populations of the PanAmerican species Excirolana brasiliensis (Cardoso & Defeo 2004).…”
Section: Reproductive Cyclementioning
confidence: 96%
“…3, showed considerable differences in the population structure of M. mactroides. The number of individuals was many times higher in 1968 compared to 2005 (up to 53 times higher in December), suggesting a much smaller reproduction success nowadays during spring time, which represents one of the two spawning seasons per year (Herrmann et al 2009a). Not merely the number of individuals can be registered as a great difference between the historical population and the recent one, but rather the bivalves in 1968 reached a much higher apSL.…”
Section: Population Structurementioning
confidence: 96%
“…donacium populations showed clear seasonal patterns in their reproductive cycles, as observed for the closely related species M. mactroides in some locations of the Atlantic coast (Herrmann et al 2009). At a local scale, previous studies have indicated that factors such as temperature, precipitation, salinity, upwelling and river discharge can regulate reproductive cycle in specific localities (Tarifeño 2008, Riascos et al 2009).…”
Section: Discussionmentioning
confidence: 55%